Hypercalcemia due to Elevated 1,25 dihydroxyvitamin D in Tophaceous Gout - Case Report and Literature Review - Ahmad, Madhia; Lee, Sunnie; Kyi, Htay Htay; Wang, Shuwei; Mahendrakar, Smitha; Yudd, Michael (Journal of Clinical Nephrology, 2024)
Granulomatous diseases can cause hypercalcemia due to elevated 1,25-dihydroxyvitamin D through the production of 1-α hydroxylase by macrophages in the granulomas. Tophaceous gout is not considered to cause this picture. However, there are a few case reports of this occurrence in tophaceous gout, as well as the description of intense 1-α hydroxylase activity in granulomas of tophi in gout patients. We review this literature, and we report a well-documented case of hypercalcemia with elevated serum 1,25 dihydroxyvitamin D in a patient with extensive tophaceous gout and tophi loaded with granulomas. An extensive work-up ruled out other causes of hypercalcemia and granulomatous diseases. Prednisone corrected the chemical abnormalities. Diffuse tophaceous gout should be considered a rare cause of hypercalcemia due to excessive 1,25 dihydroxy vitamin D.